2022
DOI: 10.1155/2022/6993034
|View full text |Cite|
|
Sign up to set email alerts
|

Multiobjective Optimization Design of Green Building Energy Consumption Based on Inorganic Thermal Insulation Nanomaterials

Abstract: In order to solve the problem that building engineering construction needs to consume a lot of energy and cause environmental pollution, which will pose a great pressure on urban resources and environment, this paper proposes that, in building engineering construction, appropriate green construction technology must be selected in combination with the actual situation, so as to effectively reduce the energy consumption of building engineering and improve the use efficiency of building engineering. Firstly, good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Complementing this, research into the practical application of green building principles, as seen in studies, provides valuable insights into the planning and construction of sustainable structures. A. L. Shimpi (2022) Innovations in building materials also play a crucial role in green construction, as demonstrated in the work of Yuan and Li (2022). Their research on inorganic thermal insulation nanomaterials underscores the importance of material science in reducing energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Complementing this, research into the practical application of green building principles, as seen in studies, provides valuable insights into the planning and construction of sustainable structures. A. L. Shimpi (2022) Innovations in building materials also play a crucial role in green construction, as demonstrated in the work of Yuan and Li (2022). Their research on inorganic thermal insulation nanomaterials underscores the importance of material science in reducing energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The science and engineering of nanotechnology have improved the high-temperature performance of concrete. The addition of nano-SiO 2 can improve the role of the thermal insulation capacity of concrete, due to the dense internal structure, increasing the specific heat capacity and reducing the thermal diffusivity [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%